Comparison of Asphalt Content Methods of Hot Asphalt Mix - Loayza León, Octavio (2025)
The composition of the hot asphalt mixture used for pavements is defined according to a design that try to meet the performance according the project in which it is to be used. Since asphalt is the binding material that provides cohesion and adhesion to the mixture, it is important to be able to quantify if the mixture produced contains the amount of asphalt established in the mix design, for that different tests have been developed to determine the content of asphalt. Although the purpose of the test methods is the same, there are doubts about the accuracy of some of them, and especially about the correlation between test procedures. This study aims to provide real results of an asphalt mix produced in a production plant, which is analyzed using the different methods and equipment to compare them with the production data and thus determine the precision and accuracy of each procedure. The results show that the methods of incineration by resistance furnace, incineration in the infrared furnace and the solvent extraction method using centrifuge do not present significant statistical differences, which is not the case with the solvent extraction method using a reflux system. The latter, despite being the one with the lowest variability, is also the most distant from the design asphalt content. However, the four methods studied are within the tolerance allowed by national regulations with respect to the asphalt content established in the blend design. In addition, as some laboratories use the gasoline extraction method as solvent instead of ACS grade trichlorethylene, the extraction test is performed using both solvents to determine whether the result with the alternative solvent is reliable. The results obtained discard it as solvent, as it does not produce statistically comparable results with the method when using trichlorethylene.